Department of mechanical engineering - Faculty of engineering University of Auckland - Yacht research Unit - Current Research Projects (2007)
To determine the sensitivity of yacht velocity to design variable variations, the VPP can output Lagrange multipliers on constraints on the design variables. These give the percentage changes in the objective for a percentage change in the design variable, other things being held constant. These values allow estimates to be made as to the usefulness of improving force models for particular aspects of the virtual yacht.